The influence of Knowledge Management Dimensions on Job Performance of Academic Staff in Higher Education institutions: An empirical Study from Saudi Arabia (an applied study on academic staff member at Shaqra University) - Shamoon, Asim (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The purpose of this paper is to study the influence of Knowledge Management Dimensions (KM) on Job Performance (JP). More importantly, this study aims to investigate the influence of dimensions of Knowledge management which is represented in (Acquiring and transferring knowledge, knowledge storage, knowledge transfer ، and knowledge application) by academic staff members at Shaqra University on their job performance which is represented (perform task, quality performance, contextual performance, level of negative performance). Moreover, Population of this study were all academic staff members from Shaqra University, that among a random sample of (46) personnel were selected for the study. Descriptive and analytical research methodology was used to collect data and to analyses the extent to which (KM) influence on (JP) in the Shaqra University. The data was analyzed by (SPSS and AMOS) the most important finding was that, there is a significant influence of knowledge management dimension with (JP) dimension.